2011
DOI: 10.1152/ajpcell.00378.2010
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial patterns of endogenous danger signal expression after wound healing and in response to lymphedema

Abstract: While acute tissue injury potently induces endogenous danger signal expression, the role of these molecules in chronic wound healing and lymphedema is undefined. The purpose of this study was to determine the spatial and temporal expression patterns of the endogenous danger signals high-mobility group box 1 (HMGB1) and heat shock protein (HSP)70 during wound healing and chronic lymphatic fluid stasis. In a surgical mouse tail model of tissue injury and lymphedema, HMGB1 and HSP70 expression occurred along a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 55 publications
7
56
1
Order By: Relevance
“…To circumvent these difficulties, we used two different mouse models to study the effects of variable degrees of lymphatic injury on IL-6 expression. We have previously shown that ALND in mice results in significant but subtle increases in arm volume peaking at 3 wk and returning to normal by 6 wk (24,39). In this model, similar to clinical findings after lymphadenectomy, the ipsilateral limb is essentially normal in appearance by 6 wk.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…To circumvent these difficulties, we used two different mouse models to study the effects of variable degrees of lymphatic injury on IL-6 expression. We have previously shown that ALND in mice results in significant but subtle increases in arm volume peaking at 3 wk and returning to normal by 6 wk (24,39). In this model, similar to clinical findings after lymphadenectomy, the ipsilateral limb is essentially normal in appearance by 6 wk.…”
Section: Discussionsupporting
confidence: 77%
“…For example, Harvey and colleagues (17) reported that mice with a heterozygous inactivating mutation of the Prox-1 gene not only have lymphatic developmental abnormalities but also become obese as adults as compared with their wild-type littermate controls. Using a surgical mouse model of axillary lymphadenectomy in which the draining lymph nodes of the forelimb are removed, our group has shown that even this relatively minor injury increases the expression of adipose differentiation genes such as CEPB-␣ and Ppar-␥ (2) as well as early inflammatory cascades in the forelimb subcutaneous tissues (39). By comparing tissues harvested from mice that had undergone axillary lymph node dissection with a more severe model of lymphatic injury in the mouse tail, we have also shown that the degree of adipose deposition is related to the severity of lymphatic obstruction and tissue inflammation (6).…”
mentioning
confidence: 99%
“…In these models, lymphatic vessel function has been investigated using different imaging techniques [3][4][5][6][7][8]. In the ALND model, lymphatic drainage patterns were examined in response to surgical removal of the ALN alone or together with the brachial LN (BLN) [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that an inability of the lymphatic system to adequately regenerate during normal wound repair may predispose the tissue to swell during secondary lymphedema (21,33). For this reason, attention has recently shifted to clarifying the regulation of lymphangiogenesis by molecules expressed during wound repair (2,10,11,21,33,35,37).…”
mentioning
confidence: 99%